A Survey of Juvenile Justice System to Protect Protecting Children's Rights: Improving the Terminology and Rehabilitation of Juvenile Offenders (Journal of Advances and Scholarly Researches in Allied Education, 2021)
The term Juvenile Justice is often heard. The only context in which it is used consistently is inreference to authorized methods of treatment and social reintegration. Juvenile is a derogatory phrase fora youngster under the legal age of criminal responsibility who has been accused or found guilty ofcommitting an offence. With the goal of eliminating the negative connotation of the word juvenile, theprovisions of the Juvenile Justice (Care and Protection of Children) Act of 2000 were enacted in India,marking the first time such an attempt had been undertaken. Juveniles formerly referred to as juveniledelinquents are now known as youth in conflict with the law, while minors previously referred to asyouth in need of care and protection are now known as juveniles in need of care and protection.